Abdominal actinomycosis - Cassinelli, Daniel; Placenza, Guillermo; Nuñez, Susana (Cirugía del Uruguay, 1974)
A rare case of actinomycosis located in the omentum majus was treated through surgical abscission of process and antibiotics. Evolution was good an patient recovered.